AI-based modules for vertical farming and protected cultivation of horticultural crops - Kumaran, G. Senthil; Kalaivanan, D.; Rathinakumari, A. Carolin; S. A., Safeena (Indian Horticulture, 2025)
The rapid advancements in Artificial Intelligence (AI) have significantly transformed traditional horticultural practices, particularly in vertical gardening and protected cultivation. As urban population increase, the demand for sustainable and space-efficient farming methods have intensified. Vertical farming and protected cultivation (like greenhouses and polyhouses) offer solutions by maximizing space and controlling environmental variables, respectively. However, achieving optimal results require precise management of resources, plant health, and environmental conditions. AI-driven systems offer a data-centric approach to address these challenges, making farming more productive, efficient, and sustainable. This article describes the role of AI modules in vertical farming and protected cultivation, examining how these technologies reduce resource usage, improve crop yields and enhance overall farming efficiency.